VISUAL DISTOPIA ZDZISLAW BEKSINSKI - Rumekso, Kunto Adi (Jurnal Industri Kreatif dan Inovatif, 2025)
Human beings have such diverse ways of perceiving events; many sink into despair, while many others give up and succumb to futility. In this discussion, we aim to examine how the Polish artist, photographer, and sculptor Zdzislaw Beksinski transforms tragedy, grief, horror, destruction, and the decay of the future into a mirror reflecting the shadows of the present and future, in every visual work he presents. The experiences and creative processes he continuously undertakes in his artistic journey seem to serve as a record or identity for art enthusiasts, critics, and even those unfamiliar with him, allowing them to understand his mindset and who he is simply by viewing his works. Zdzislaw's genius has made him an inspiration for subsequent artists to dare to dive into and embrace a tragic movement, the offspring of surrealism that embraces nightmares and pessimism, known as the Dystopian movement.